Пролетали лебеди: рассказы / Федор Абрамов - Абрамов Федор Александрович ([Библиотечная серия], 1985)
Экземпляры: ф.2 (20180921) / Инвентарный номер: 11031 / Цена: 00.55 / Авт.знак: А16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6